Mallorca, Kulturgeographische Wandlungen als Auswirkung der Insellage - Mayer, Eberhard (ERDKUNDE, 1966)
It is attempted to interpret typical traits of Mallorca’s cultural geography as the expression of its island situation. Phenomena obeying the laws of physical geography, such as the island’s climate, or the strongly endemic character of its vegetation, are deliberately not taken into account. At the present time, in which we should expect strong tendencies towards an homogenous cultural landscape, structural elements basically influenced by situation are making new differentiations clear. The ’individual’ becomes perceivable against the ’background of the typical’ (21, p. 28) and the ’situational viewpoint’ is thus the ’container, in which this perception maintains the specific geographic order’ (Lautensach 20, p. 4).